THE FACTORS THAT INFLUENCING DECISION OF SCIENCE PROGRAM HIGH SCHOOL STUDENTS IN DETERMINING MANAGEMENT STUDY PROGRAM MAJOR (Case Study at STIE Ciputra Makassar) - Dina Hutapea; Agus Arman; Cindy Tanesia (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study was to find out the factors that influence high school students in the science program to choose to study in the Management study program at STIE Ciputra Makassar. The population in this study were all new students of STIE Ciputra Makassar who at the time of high school were a science program but chose the Management study program. The number of samples that meet the criteria in this study are 72. The study was conducted in 2021 using a survey method by distributing questionnaires to respondents using a google form. The analytical tool used is the Chi Square Test. The results of the study conclude, the main factors that influence the respondents' decisions are: The first factor X2 wants to continue the family business, the second factor X3 wants to set up their own business, the third factor X6 wants to be a company manager, the fourth factor X7 is directed by parents/guardians, and fifth factor X8 wants to learn business management. Keywords: Factors, Choosing A Social Studies Study Program, High School